Phytochemical Assay and Antioxidant Activity against DPPH of Ethanol Extract from Kenaf Leaf (Hibiscus cannabinus L.) - Rusmini Rusmini; Dwinita Aquastini; Riama Rita Manullang; Daryono Daryono; Ali Sadikin; Hadi kuncoro (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2019)
Kenaf (Hibiscus cannabinus L.) is an environmentally friendly natural fiber-producing plant that can produce diversified products, such as paper, wallcover, car interior, geotextile, soil safer, fiber drain, particle board, and plastic reinforcement as well as biofuel industry raw materials. Kenaf plant is a plant that has been only part of the fibers of the stem alone so that many unprofitable side products such as kenaf leaves after harvesting only as a waste. In Africa the leaves of kenaf are widely used as medicine This study aims to analyze phytochemical compounds and study the antioxidant activity of the kenaf leaf. The study started by doing phytochemical test and analyzing antioxidant in kenaf leaf and then testing its antioxidant activity with DPPH method. The results showed that the leaves of kenaf contain secondary metabolites of phytochemical compounds such as flavonoids, alkaloids, steroids, saponins, carbohydrates and tannins and have antioxidant activity that is quite good that is 44.4813 ppm.